Practice Consolidation in Otolaryngology: The Decline of the Single-Provider Practice. Issue 1 (February 2022) - Quereshy, Humzah A.; Quinton, Brooke A.; Ruthberg, Jeremy S.; Maronian, Nicole C.; Otteson, Todd D.
Objective: To observe trends in practice consolidation within otolaryngology by analyzing changes in size and geographic distribution of practices within the United States from 2014 to 2021. Study Design: Retrospective analysis based on the Physician Compare National Database from the US Centers for Medicare and Medicaid Services. Setting: United States. Methods: Annual files from the Physician Compare National Database between 2014 and 2021 were filtered for all providers that listed "otolaryngology" as their primary specialty. Organization affiliations were sorted by size of practice and categorized into quantiles (1 or 2 providers, 3-9, 10-24, 25-49, and ≥50). Both the number of practices and the number of surgeons within a practice were collected annually for each quantile. Providers were also stratified geographically within the 9 US Census Bureau divisions. Chi-square analysis was conducted to test significance for the change in surgeon and practice distributions between 2014 and 2021. Results: Over the study period, the number of active otolaryngology providers increased from 7763 to 9150, while the number of practices fell from 3584 to 3152 in that time span. Practices with just 1 or 2 otolaryngology providers accounted for 80.2% of all practices in 2014 and fell to 73.1% in 2021. Similar trends were observed at the individual provider level. Regional analysis revealed that New England had the largest percentage decrease in otolaryngologists employed by practices of 1 or 2 active providers at 45.7% and the Mountain region had the lowest percentage decrease at 17.4%. Conclusion: The otolaryngology practice marketplace has demonstrated a global trend toward practice consolidation.